Risk Factor Analysis of Soil-Transmitted Helminth Infections among Scavengers at the Denpasar City Landfill – Bali - Elvera Sukma Daniel; I Made Subrata; Anak Agung Sagung Sawitri; Heri Setiyo Bekti (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Background: Soil-transmitted helminth (STH) infection is a public health concern, particularly in developing countries, including Indonesia. Scavengers are a high-risk group due to their direct contact with garbage that is potentially contaminated with worm eggs. This study aims to determine the prevalence of STH infection and risk factors associated with STH infection among scavengers at a landfill in Denpasar, Bali. Methods: This research approach was an observational study with a cross-sectional design involving 101 scavengers as respondents. Data were collected through interviews using questionnaires, observation of personal hygiene behavior, and nail clipping examination to detect the sedimentation concentration method. Results: The results showed that the prevalence of STH infection was 37.6%. Factors significantly associated with STH infection were knowledge and nail hygiene. Meanwhile, hand washing habits, footwear use, personal hygiene, environmental sanitation, and deworming medication did not show a significant association. Conclusion:  These results emphasize the importance of enhancing knowledge and nail hygiene practices as a means of preventing STH infections. Continuous health education as a means of promoting clean and healthy living habits among scavengers need to be improved as a preventive measure to reduce the risk of STH transmission